Inclusive Inclusive Education as An Effort to Deradicalize Religion in Indonesia - Zulaikhah, Siti; Gani, Ainal; Misbah, M.; Setiyono, Agus (Future Science / FSH-PH Publications, 2023)
Inclusive-based Islamic religious education is an innovative and strategic approach to preventing religious radicalism. Inclusive Islamic religious education is also a form of Islamic education reform that emphasizes anti-discrimination, tolerance and mutual respect. This study aims to determine inclusive-based Islamic religious education in preventing religious radicalism in Indonesia. A qualitative method with the type of library research, examines a variety of related data, originating from the main data sources as well as supporting data sources that have a direct link with the research. The data obtained were then analyzed by conducting content analysis. The results of this study are in the form of findings relating to the implementation of inclusive-based Islamic religious education in preventing religious radicalism, namely it is found that (a) the goals of religious education are ideological-absolutistic or oriented towards pluralist-inclusive (b) the curriculum of religious education is more oriented towards rigid laws and exclusive into a love-oriented curriculum that is inclusive (c) normative-textual material becomes normative-contextual (d) exclusive-doctrinaire educators become inclusive-moderate educators (tawasuth). (e) The textualist-scriptura list learning strategy becomes an objective-positive approaches.